2015
DOI: 10.1371/journal.pone.0119477
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Analogue of Hirsutine as an Anti-Hypertension and Vasodilatary Agent Both In Vitro and In Vivo

Abstract: In this paper, an analogue of hirsutine (compound 1) has been synthesized and evaluated as an anti-hypertension agent, which exhibits extraordinary effects on the contractile response of thoracic aorta rings from male SD rats in vitro (IC50 = 1.129×10-9±0.5025) and the abilities of reducing the systolic blood pressure (SBP) and heart rate (HR) of SHR in vivo. The mechanism investigation reveals that the vasodilatation induced by compound 1 is mediated by both endothelium-dependent and -independent manners. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Hirsutine, a major indole alkaloid (Fig. 1a ), derived from U. rhynchophylla , has attracted a great deal of interest because of its wide range of biological activities such as cardioprotective, anti-hypertensive, and anti-arrhythmic activities 6 , 7 . It has recently been shown that hirsutine exhibits anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Hirsutine, a major indole alkaloid (Fig. 1a ), derived from U. rhynchophylla , has attracted a great deal of interest because of its wide range of biological activities such as cardioprotective, anti-hypertensive, and anti-arrhythmic activities 6 , 7 . It has recently been shown that hirsutine exhibits anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…Hirsutine isolated from U. rhynchophylla extract was found to decrease intracellular calcium concentrations in rat aortas by inhibiting the calcium channels and effecting calcium stores [51]. Moreover, it showed a vasodilated, negative chronotropic, and antiarrhythmic effect.…”
Section: Cardiovascular Activitymentioning
confidence: 98%
“…Eugenol from the plant was isolated and was shown to be responsible for observed effects. Alkaloids such as; hirsutine, rhynchophylline and isorhynchophylline, isolated from the plant, Uncaria rhynchophylla, have been demonstrated to be the mediators of observed vasodilatory property (Zhu et al , 2015;Shi et al , 2003). In in vitro experiments, two cumarin glycosides coded as DC-2 and DC-3 isolated from D. carota, were tested for their inhibitory response against K + induced depolarization and contraction which suggested that the glycosides action is through blockade of calcium channels (Gilani et al , 2000).…”
Section: Traditional Medicinal Plants With Reported Mode Of Action Wmentioning
confidence: 99%
“…Blockade of Calcium channel (Zhu, Yang, 2015;Wu et al , 1980;Shi, Yu, 2003;Horie, Yano, 1992) (Ojulari, Olatubosun, Ghayur and Gilani, 2005;Elkhishin and Awwad, 2009) Plasma Renin Activity Assay Elevated in patients with essential hypertension and suppressed in patients with hypertension due to primary aldosteronism (Gunnells Jr et al , 1967) 2…”
mentioning
confidence: 99%